SISTEM INFORMASI BERBASIS ANDROID SEMABAI STRATEGI PEMASARAN SPAREPART MOTOR TOKO MAJU JAYA - Afian Dio Firmansyah; Kasmi Kasmi (YHMM PUBLISHING, 2023)
At this time technology is getting more sophisticated, and some entrepreneurs are starting to issue their products, especially motorcycle parts, various variations of complete spare parts machines using the benefits and disadvantages. This will make it difficult for buyers to make the right decisions and be shown using the right decision for the needs of the motorcycle. With so many spare parts as fast as motorbikes, more and more brands and types of motorbikes spare parts are being produced with their respective advantages and disadvantages. choosing which one is best for the buyer is not easy. Therefore, an Android-based system was created to help buyers identify motorcycle spare parts according to their preferences and preferences. With this Android, buyers will be directed to be able to choose the best quality. At the same time, the data collection method uses observation and case studies that occur. This research results in a data framework that can be used to search for spare parts at Toko Maju Jaya from category, brand, type, and price. The conclusion obtained from this research is to create an Android-based motorcycle spare part promotion system to facilitate the promotion or introduce spare parts to buyers